2008
DOI: 10.1161/strokeaha.108.189696
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Stroke in Infants and Children

Abstract: Purpose— The purpose of this statement is to review the literature on childhood stroke and to provide recommendations for optimal diagnosis and treatment. This statement is intended for physicians who are responsible for diagnosing and treating infants, children, and adolescents with cerebrovascular disease. Methods— The Writing Group members were appointed by the American Heart Association Stroke Council’s Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
385
1
29

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 878 publications
(425 citation statements)
references
References 517 publications
(466 reference statements)
10
385
1
29
Order By: Relevance
“…Also, relation to prothrombotic disorders is raised in PFO patients with cerebral EE. Furthermore, recurrence of stroke is estimated in this age group at 25-30% [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, relation to prothrombotic disorders is raised in PFO patients with cerebral EE. Furthermore, recurrence of stroke is estimated in this age group at 25-30% [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Although AF is a rare cardiac cause of stroke in children, in opposition to congenital heart lesions or valvular diseases [24], its presence is associated with high risk of stroke, and both increased mortality and stroke recurrence [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations and treatment guidelines have largely been extrapolated from adult data. Three guidelines exist to guide the management of pediatric stroke, including the American College of Chest Physicians Guidelines [126], the American Heart Association Guidelines [127], and the Royal College of Physicians guidelines from the United Kingdom. Recommendations in these guidelines are based on an expert and consensus opinion, and in some instances are diverging in their interpretation of the data and on specific clinical management points [128].…”
Section: Current Developmentsmentioning
confidence: 99%
“…Perinatal and neonatal strokes give an incidence of 10 to 18 in 100,000 live births, while studies have reported rates of up to 63/100,000. 7 In view of its different clinical manifestations, its diverse causes and low suspicion for stroke in pediatrics, these data may underestimate the true incidence of stroke in this group. Stroke recurrence in children can reach 20%, and in the presence of multiple risk factors recurrence can be as high as 42%.…”
Section: Epidemiological Featuresmentioning
confidence: 99%
“…81 The anticoagulant therapy, either in the acute phase of stroke or for the chronic management, is one of the major issues described in the 2008 guidelines in Chest 82 and the American Heart Association (AHA). 7 In AIS, the Chest guidelines recommend use of UFH or LMWH or aspirin (1 mg/kg/day) until cardioembolic and dissection subtypes of stroke are excluded. The AHA recommendation addresses use of UFH or LMWH up to 1 week until the cause is determinate.…”
Section: Anticoagulant and Antiplatelet Therapymentioning
confidence: 99%